2019
DOI: 10.5551/jat.rv17030
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Statin Intolerance

Abstract: Statins are the main treatment for hypercholesterolemia and the cornerstone of atherosclerotic cardiovascular disease prevention. Many patients taking statins report muscle-related symptoms, one of the most important causes of statin treatment discontinuation, which is associated with an increased risk of cardiovascular events. Therefore, it is important to identify patients who are truly statin intolerant to avoid unnecessary discontinuation of this beneficial treatment. Some studies indicate that not all mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 62 publications
1
46
0
2
Order By: Relevance
“…We have also encountered patients whose statinassociated muscle symptoms appeared to respond to supplements of coenzyme Q10, some of which were self-initiated. We agree with Alonso et al 1) that the current evidence from a meta-analysis of randomized controlled trials does not support the use of coenzyme Q10 for statin-related symptoms, and anecdotal case reports do not provide high-quality supportive evidence. Nevertheless, we would suggest that it is worth conducting a trial of coenzyme Q10 in some patients with apparent statin intolerance as it is essential for patients to continue statin therapy when it is truly indicated.…”
Section: To the Editorsupporting
confidence: 74%
See 1 more Smart Citation
“…We have also encountered patients whose statinassociated muscle symptoms appeared to respond to supplements of coenzyme Q10, some of which were self-initiated. We agree with Alonso et al 1) that the current evidence from a meta-analysis of randomized controlled trials does not support the use of coenzyme Q10 for statin-related symptoms, and anecdotal case reports do not provide high-quality supportive evidence. Nevertheless, we would suggest that it is worth conducting a trial of coenzyme Q10 in some patients with apparent statin intolerance as it is essential for patients to continue statin therapy when it is truly indicated.…”
Section: To the Editorsupporting
confidence: 74%
“…The recent article in this journal by Alonso and colleagues provides a helpful review of the diagnosis and management of statin intolerance 1) . The authors listed the major risk factors for statin-associated muscle symptoms; however, they did not include Asian ethnicity in the list.…”
Section: To the Editormentioning
confidence: 99%
“…The benefits and risks of continuing, temporarily suspending, and discontinuing statin treatment need to be weighed up. Additional patient counselling involves discussion about the nocebo effect and complimentary therapeutic lifestyle changes (e.g., smoking cessation, blood pressure control, adopting the Mediterranean diet) [67,266]. There is no gold-standard diagnostic method nor a validated questionnaire for SRM, although a myalgia clinical index score has been proposed by the NLA [267].…”
Section: Management Of Srmmentioning
confidence: 99%
“…3 Similarly, observational studies have shown that a substantial proportion of patients cannot or do not take statins as prescribed due to intolerance, non-adherence, or barriers to accessing medication, with adherence rates ranging from 25% to 60% in different clinical settings. 4 Although many definitions of statin intolerance have been proposed, 5,6 a pragmatic operational definition may be the inability to tolerate statin treatment, usually due to the occurrence of symptoms and/ or laboratory abnormalities.…”
Section: Introductionmentioning
confidence: 99%